1989
DOI: 10.1002/jpln.19891520207
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization and turnover of soil phosphorus in the rhizosphere

Abstract: Recent progress in methods enables a better understanding of the turnover of P in the rhizosphere. Examples of this progress are the separation of soil layers differing in proximity to the roots, improved methods for extraction and fractionation of soil P, application of 32P isotope dilution analysis to follow P fluxes between various fractions and direct determination of microbially bound P and of root phosphatases. These methods were combined to investigate the following aspects –labile P pools, the P fluxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

1993
1993
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 25 publications
(5 reference statements)
0
25
0
3
Order By: Relevance
“…It has been suggested that, due to their compact secondary structure, both free DNA and RNA might become stabilized in soil following the release from lysing cells (Nannipieri et al, 1986). In view of the high turnover of organic phosphorus in the rhizosphere (Helal and Dressler, 1989), the importance of secretory nucleolytic enzymes for effective phosphorus acquisition of plants is evident. This is further demonstrated by normal growth and development of Arabidopsis plants on synthetic media containing purified nucleic acids as the only source of phosphorus (S. Abel, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that, due to their compact secondary structure, both free DNA and RNA might become stabilized in soil following the release from lysing cells (Nannipieri et al, 1986). In view of the high turnover of organic phosphorus in the rhizosphere (Helal and Dressler, 1989), the importance of secretory nucleolytic enzymes for effective phosphorus acquisition of plants is evident. This is further demonstrated by normal growth and development of Arabidopsis plants on synthetic media containing purified nucleic acids as the only source of phosphorus (S. Abel, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, soil IP 5ϩ6 contents have been strongly correlated with phosphate sorption capacity (McKercher & Anderson 1968b). However, Helal & Dressler (1989) noted that the addition of Na-phytate to soil displaced Fe as well as orthophosphate, indicating that the reaction was not a simple phytate/orthophosphate exchange, but involved the modification of soil properties related to sorption. For example, changes in electrochemical properties almost certainly contribute (Celi et al 1999).…”
Section: Structure Nomenclature and Chemistry Of Inositol Phosphatesmentioning
confidence: 99%
“…Approximately 40 % of organic soil P are found in the inositol P fractions whereas 7 % are bound in lipids and nucleic acids (Dalal, 1977). It is known that organic P is involved to a great extent in the dynamics and cycling of soil P (Helal and Sauerbeck, 1984;Helal and Dressler, 1989).…”
Section: Introductionmentioning
confidence: 99%